VD_FINDINFO AM 29/12 - 35/2012 vom 31. Mai 2012 - VD Tribunal cantonal (2012)
COMMANDEMENT DE PAYER, REQUÊTE DE MAINLEVÉE, COMPÉTENCE RATIONE LOCI, DÉCISION D'IRRECEVABILITÉ | 84 al. 1 LP, 42b al. 1 ch. 2 LVLP, 82 LPA-VD